Exploring the concentration‐dependent actions of interferon‐τ on bovine neutrophils to understand the process of implantation. Issue 12 (1st September 2018) - Manjari, P.; Hyder, Iqbal; Kapoor, Suresh; Senthilnathan, M.; Dang, A. K.
Abstract: Interferon‐τ (IFNT) is a major cytokine produced by the ruminant trophoectoderm during the peri‐implantation period exerting immunomodulatory actions on various cells including neutrophils. The current in vitro study was undertaken to analyze the concentration‐dependent effects of IFNT on neutrophil gene dynamics to understand its possible role in implantation process. The neutrophils were isolated from the blood of heifers and were cultured subjecting them to different IFNT concentrations (1, 5, or 10 ng/mL). The gene‐expression patterns of different interferon‐stimulated genes, l ‐selectin, CD31, CD11b, and progesterone‐induced blocking factor (PIBF) were analyzed by quantitative real‐time PCR. It was observed that at lower concentrations of IFNT, the IFI16, l ‐selectin, ISG15, and PIBF were upregulated, whereas at higher concentrations the same were down regulated. At all the experimental concentrations, IFI44, OAS1, MX genes were significantly upregulated and CD31, CD11b were significantly downregulated. At lower concentrations of IFNT, the neutrophil activity with respect to chemoattraction is stimulated, whereas at higher concentrations the same is reduced. Hence, it can be concluded that IFNT exerts concentration‐dependent actions on neutrophil gene‐expression dynamics indicating a fine modulation of its activity depending upon the temporal variation in its destined functions ultimately leading to successful implantation. Abstract : The interferon‐τ (IFNT) affects the gene‐expression dynamics of neutrophils in a concentration‐dependent manner. At lower concentrations IFNT favors neutrophil‐mediated inflammation by upregulating selective interferon‐stimulated genes. At higher concentrations IFNT inhibits physical and functional activity of neutrophils by down regulating the same selective genes. Some of the neutrophil genes are expressed consistently independent of concentration levels, and these stably expressed genes are the ones that consistently promote implantation.